Endoscopic Carpal Tunnel Release Via a Monoportal Approach Die endoskopische Karpaltunnelspaltung im monoportalen Verfahren - Hessenauer, Maximilian Emanuel Thomas; Horch, Raymund E. (Zentralblatt für Chirurgie, 2019)
Carpal tunnel syndrome is a very common condition in hand surgery. The gold standard in therapy is the surgical release of the flexor retinaculum. Endoscopic carpal tunnel release provides superior convalescence and patient safety. In this video paper, we demonstrate endoscopic carpal tunnel release via a monoportal approach and report our experience in treating over 800 cases.
CRIS-Team Scopus Importer:2019-06-28
Keywords: carpal tunnel; endoscopic; monoportal